Role of eosinophil counts in mediating the association between asthma and colon cancer - Zhi‐Qing Zhan; Ze‐Min Huang; Zhi‐Xin Xie; Hao‐Bin Zhou; Yu‐Hua Luo; Pei‐Zhen Chen; Tian‐Ye Luo; Baoqing Sun; Zhangkai J. Cheng (Clinical and Translational Allergy)
Abstract Background Epidemiological findings regarding the association between asthma and the risk of colon cancer (CC) are inconsistent. The causality and potential molecular mechanisms underlying asthma, eosinophil count, and CC remain unknown. Methods We performed Mendelian randomization (MR) analysis to investigate the causality between asthma and CC and attempted to demonstrate that asthma indirectly affects CC mediated by eosinophil count through mediation analysis. Sensitivity analyses and multivariable MR were performed to test the robustness of our findings. Multiple bioinformatics tools were applied to further investigate the underlying mechanisms related to eosinophils that contribute to the pathogenesis of both asthma and CC. Results MR with mediation analyses suggested that eosinophil count may play a role in the mechanism through which asthma reduces the risk of CC. Our bioinformatic analyses identified PPP1R14A as a potential therapeutic target and an eosinophil‐associated biomarker for CC patients. Higher expression of PPP1R14A may be associated with a poorer prognosis in CC patients. Additionally, the lysosome pathway emerges as a shared eosinophil‐related pathway in both asthma and CC. Conclusions Eosinophils may contribute to a lower risk of CC in patients with asthma. PPP1R14A is a potential therapeutic target and biomarker for CC.